Matching Grants as a Strategy for Enterprise Development - Anna Jennifer L. Umlas; Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2023)
This paper provides a short overview on the potential use of matching grants as a strategy to spur private sector investment. Specifically, it describes the design and initial implementation of the conditional matching grant scheme under the Rural Agro-enterprise Partnership for Inclusive Development and Growth (RAPID Growth) Project. The focus is on the use of matching grants as a strategy to finance productive investments of farmer organizations or private micro and small enterprises.
Keywords: 330; matching grant; RAPID Growth project